2012
DOI: 10.1002/mus.23293
|View full text |Cite
|
Sign up to set email alerts
|

Membrane dysfunction in Andersen‐Tawil syndrome assessed by velocity recovery cycles

Abstract: MVRCs combined with repetitive stimulation differentiated ATS patients from controls more effectively than the conventional long-exercise test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…In contrast to the high sensitivity of MRRP to temperature, ESN and also the ISI for peak supernormality did not change significantly in the temperature range of 30°–34°C. In several earlier studies, ESN has been shown to be a highly valuable parameter to detect changes in muscle membrane potential 2–7. If adequate temperature control is not possible, ESN should be considered the most suitable parameter to detect changes of muscle membrane properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the high sensitivity of MRRP to temperature, ESN and also the ISI for peak supernormality did not change significantly in the temperature range of 30°–34°C. In several earlier studies, ESN has been shown to be a highly valuable parameter to detect changes in muscle membrane potential 2–7. If adequate temperature control is not possible, ESN should be considered the most suitable parameter to detect changes of muscle membrane properties.…”
Section: Discussionmentioning
confidence: 99%
“…The depolarizing afterpotential is associated with a period of increased conduction velocity, that is, supernormality. Recent studies have demonstrated that this method is very sensitive to changes in membrane potential 2–7. However, the effects of changes in muscle temperature have not been investigated previously.…”
mentioning
confidence: 99%
“…The recording technique was similar to that developed for the brachioradialis muscle, but adapted to tibialis anterior (TA) . Recordings were performed on the distal third of TA, with a monopolar stimulating needle inserted perpendicularly within 1 cm of the palpated distal extent of the muscle.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the scope of the tests has been broadened by adding 2 repetitive stimulation protocols, because muscle activation is known to precipitate muscle dysfunction in some muscle disorders . The first of these studies described altered muscle membrane function in patients with Andersen–Tawil syndrome, a rare type of periodic paralysis due to defective inward rectifier channels …”
mentioning
confidence: 99%
“…Changes of muscle membrane potential and alterations of muscle ion channel function can be assessed in vivo by recording multi‐fiber muscle velocity recovery cycles (MVRCs) . The technique is based on the principle that an elicited action potential induces a depolarizing afterpotential, which declines in 2 phases over approximately 1 s (early and late supernormality) to its resting membrane potential .…”
mentioning
confidence: 99%